Bibliometric analysis of the use of pathological techniques in camel research - Ahmed Aljazzar (Open Veterinary Journal)
Background: Camel pathology research has evolved significantly over the past five decades, reflecting the growing recognition of camels' importance in agriculture, zoonotic disease control, and economic contributions. However, there has been limited evaluation of research trends, thematic advancements, and international collaborations in this field.